Application of deep eutectic solvents for the extraction of phenolic compounds from extra‐virgin olive oil. Issue 20 (9th March 2020) - Fanali, Chiara; Posta, Susanna Della; Dugo, Laura; Russo, Marina; Gentili, Alessandra; Mondello, Luigi; De Gara, Laura
Abstract: A HPLC–DAD/ESI–MS method has been developed and validated for the analysis of the most representative phenolic compounds in extra‐virgin olive oil (EVOO) samples using a green extraction approach based on deep eutectic solvents (DESs) at room temperature. We examined ten DESs based on choline chloride and betaine in combination with different hydrogen bond donors comprising six alcohols, two organic acids, and one urea. Five phenolic compounds, belonging to the classes of secoiridoids and phenolic alcohols, were selected for the evaluation of extraction efficiency. A betaine‐based DES with glycerol (molar ratio 1:2) was found to be the most effective for extracting phenolic compounds as compared to a conventional solvent. The optimization of the extraction method involved the study of the quantity of water to be added to the DES and evaluation of the sample‐to‐solvent ratio optimal condition. Thirty percent of water added to DES and sample to solvent ratio 1:1 (w/v) were selected as the best conditions. The chromatographic method was validated by studying LOD, LOQ, intraday and interday retention time precision, and linearity range. Recovery values obtained spiking seed oil sample aliquots with standard compounds at 5 and 100 μg/g concentration were in the range between 75.2% and 98.7%.